2017
DOI: 10.11113/jt.v79.11899
|View full text |Cite
|
Sign up to set email alerts
|

Helical Twisted Effect of Spiral Pipe in Generating Swirl Flow for Coal Slurries Conveyance

Abstract: This paper proposes methods to reduce energy consumption for the transportation of coal slurries. Spiral pipe is one of the methods that can improve drag reduction at certain velocity as well as prevent decomposition at the pipe bottom and generate homogenous particles distribution. The objective is to investigate the influence of using spiral pipe to pressure drop and homogeneity of coal slurries. The pipe angles (β) are 140, 230, 400 and 560, the pipe test loop is set up with entrance length 3000 mm. Pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…al. 25) . The above equation of Re' is quoted from Benslimane et al 26) and Kristiawan et al 27) that simplify Re' calculation from Metzner et al 28) to make them more relevant to the method of this investigation.…”
Section: Methods and Experimental Setupmentioning
confidence: 99%
“…al. 25) . The above equation of Re' is quoted from Benslimane et al 26) and Kristiawan et al 27) that simplify Re' calculation from Metzner et al 28) to make them more relevant to the method of this investigation.…”
Section: Methods and Experimental Setupmentioning
confidence: 99%
“…Compared with traditional circular pipes, spiral pipes have a lower critical velocity of flow for the same slurry [19]. Yanuar et al [20] investigated solid-liquid two-phase flow via spiral pipes at various angles. The study found that employing spiral pipes improved the homogeneity of a coal slurry by 22%, while also reducing the conveying resistance by around 30%.…”
Section: Introductionmentioning
confidence: 99%